2017
DOI: 10.1016/j.jtho.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Stage Groupings in the Eighth Edition of the TNM Classification for Lung Cancer

Abstract: This study provided an external validation of the stage groupings in the eighth edition of the TNM classification for lung cancer among surgically treated Chinese patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…To predict the clinical significance of CD44 expression, we analyzed the associations between CD44 expression and clinicopathological features in NSCLC. There was no significant difference between CD44 expression and age, sex, smoking status, pathology type, N classification or TNM stage ( 22 ). However, the level of CD44 expression was positively associated with an advanced T classification (P<0.05; Table I ).…”
Section: Resultsmentioning
confidence: 94%
“…To predict the clinical significance of CD44 expression, we analyzed the associations between CD44 expression and clinicopathological features in NSCLC. There was no significant difference between CD44 expression and age, sex, smoking status, pathology type, N classification or TNM stage ( 22 ). However, the level of CD44 expression was positively associated with an advanced T classification (P<0.05; Table I ).…”
Section: Resultsmentioning
confidence: 94%
“…Thus, it is important to determine the prognostic effect of EGFR mutation after adjusting for these variables in order to prevent false positive or false negative results. In this context, one of the strengths of the present study was that pathological stage, adenocarcinoma subtype, and solid portion size, all of which are powerful prognostic factors with a potential association with EGFR mutation, were included in the analysis . The substantial discrepancy between the current study findings and the reported results in the literature might be attributable to differences in the included variables.…”
Section: Discussionmentioning
confidence: 77%
“…The TNM staging system of the 8 th edition AJCC, demonstrated better survival stratification of T staging than the 7 th edition (10,11). Stage N2 disease was separated into subgroups of stage IIIA and IIIB depending on whether T1-2 or T3-4 was present.…”
Section: Discussionmentioning
confidence: 99%